A review of womanhood and motherhood in selected novels of Shashi Deshpande - Sheril (Universal Research Reports, 2017)
Shashi Deshpande has received prestigious Sahitya Academy Award for her 5th novel,' That Long Silence' published in 1989, she uses very first person narrative to register female's protest against male dominated society in novel. Her protagonist is an educated, middle class female that turns into a helpless victim in marital life and also its duties. Her females protagonists are in continual search for their' Selves'. novel opens with Jaya as well as her husband Mohan shifting back into old Dadar flat in Bombay from the lavish huge house of theirs at Churchgate. Their 2 kids Rati and Rahul are away on an extended trip with the family friends of theirs. Jaya's 2 days remain in Dadar flat is in quiet resentment paves way for self criticism and also self evaluation. In her re-examination of the married life of her, she discovers that she's not really satisfied.